Hyperaldosteronism: types, clinical characteristics, and treatment - Alsyamy, Areej M.; Kashkari, Amnah T.; Alazdi, Fawaz A.; Dalati, Abdulmonem T.; Alawadi, Mohammed M.; Hawari, Emad S.; Nassar, Mohammed M.; Hennawi, M. Mohanad I. A.; Alaslani, Hassan H.; Albayshi, Ashjan A.; Fatani, Mohammed L. (International Journal Of Community Medicine And Public Health, 2021)
Cases with hyperaldosteronism might be asymptomatic in many events. Therefore, the diagnosis can be missed. However, the usual presentation for many patients has been reported to be a refractory elevation in the blood pressure which might be mild to severe. Based on the type of hyperaldosteronism and the diagnosis, the treatment of these conditions should be established. Therefore, it can be concluded that the treatment is specific to the management of the underlying etiology, and managing the clinical characteristics and associated complications. This present literature review aims to provide evidence regarding the types, clinical characteristics, and treatment of aldosterone based on data from the current investigations in the literature. Different clinical phenotypes have been reported for the condition. Nevertheless, the disease can be broadly classified into primary and secondary hyperaldosteronism based on the pathophysiology and etiology of the condition. Clinical characteristics might not be diagnostic since they are very non-specific, despite being common in these patients, as hypokalemia and hypertension. Therefore, clinicians should be aware of conducting the necessary diagnostic approaches before establishing the diagnosis. Management of these patients requires the integration of different approaches, including surgical and medical treatment. Perioperative care is important because it may lead to unfavorable consequences if neglected.